2019
DOI: 10.1371/journal.pone.0212792
|View full text |Cite
|
Sign up to set email alerts
|

Obesity measured as percent body fat, relationship with body mass index, and percentile curves for Mexican pediatric population

Abstract: In Mexico, the increase in childhood obesity is alarming. Thus, improving the precision of its diagnosis is expected to impact on disease prevention. We estimated obesity prevalence by bioimpedance–based percent body fat (%BF) and body mass index (BMI) in 1061 girls and 1121 boys, from 3 to 17 years old. Multiple regressions and area under receiver operating curves (AUC) were used to determine the predictive value of BMI on %BF and percentile curves were constructed. Overall obesity prevalence estimated by %BF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 35 publications
3
41
0
1
Order By: Relevance
“…Similar to our results, Costa-Urrutia et al have recently reported that between 8% and 17% of Mexican children and adolescents may show healthy BMI values, although they may have an excess of bioimpedance-based adiposity, meaning males with >25% and females >30% of percent body fat. In contrast, we described adiposity by means of FMI measured by DXA, and considered possible misclassification according to the proportion of subjects categorized as healthy according to BMI values but showing FMI values equal to or above their overweight or obese peers' means [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our results, Costa-Urrutia et al have recently reported that between 8% and 17% of Mexican children and adolescents may show healthy BMI values, although they may have an excess of bioimpedance-based adiposity, meaning males with >25% and females >30% of percent body fat. In contrast, we described adiposity by means of FMI measured by DXA, and considered possible misclassification according to the proportion of subjects categorized as healthy according to BMI values but showing FMI values equal to or above their overweight or obese peers' means [13].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its simplicity, BMI has become the standard tool to diagnose OW/OB, and it has shown a good correlation with adiposity in epidemiological studies. Nevertheless, at the individual level, BMI may misclassify subjects at risk [13,14] especially in populations were reference values are not reported, as in the case of Mexican children and adolescents [13]. Having a more direct measurement of adiposity may provide more reliable data to identify relationships between OL habits and their impact on health.…”
Section: Introductionmentioning
confidence: 99%
“…The comparison is shown in Table 1 as well as Figures 5 and 6. However, results are different when we base our comparison on FM percentage (25% for boys, 30% for girls) vs. BMI [4,7].…”
Section: Childhood Obesity In the Mexican Populationmentioning
confidence: 91%
“…There is still much controversy about which indicator is ideal for measuring overweight or obesity. Some authors are inclined towards the use of FM%, asserting that it has a high correlation with BMI [4], however, as height is not taken into account, the use of FM % is debated. Recent studies refer to the current need for the accurate assessment of body composition for a complete follow up in weight gain and weight loss scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The gold standard in diagnosing obesity as well as the relationship between the different measures of obesity and other chronic diseases remains debatable. Studies within Mexican and Caucasians population have reported that prevalence of obesity in their study population differ depending on whether the classification was done with BMI or %BF [18, 19]. In a study among Australia women they showed that waist circumference and waist-to-hip ratio were better predictors of cardiovascular disease risk than BMI [20] whereas in a Nigerian population study, BMI in addition to both waist circumference and waist-to-hip ratio were excellent predictors of cardiovascular risk [16].…”
Section: Discussionmentioning
confidence: 99%